Callochiton Gray 1847 - Dell'Angelo, Bruno; Landau, Bernard M.; Sosso, Maurizio; Taviani, Marco (Zenodo, 2020)
Genus Callochiton Gray, 1847 Type species. Chiton laevis Montagu, 1803 ( non Pennant, 1777) = Callochiton septemvalvis (Montagu, 1803), by subsequent designation (Gray 1847). Distribution. Mostly tropical and subtropical regions of the Indo-Pacific (including Japan, absent from the northeastern Pacific). In the Atlantic Ocean, it is restricted to the sub-Antarctic and the eastern part further north. The fossil record extends back to the lower Oligocene of New Zealand (Ashby 1929), the Miocene of Europe (Bałuk 1984; Dell’Angelo et al. 2016), Argentina (Urteaga et al. 2011) and Australia (Ashby 1939) and the Pleistocene of Japan (Itoigawa et al . 1976). Published as part of Dell'Angelo, Bruno, Landau, Bernard M., Sosso, Maurizio & Taviani, Marco, 2020, Late Pleistocene Red Sea Mollusca: 1. Polyplacophora, pp. 401-449 in Zootaxa 4772 (3) on page 409, DOI:10.11646/zootaxa.4772.3.1, http://zenodo.org/record/3819654